A case series of brain abscesses: an eleven-year retrospective single center study - Rami Waked; Hassan Tarhini; Hussein Mansour; Gebrael Saliba; Nabil Chehata; Marie Chedid; Elie Haddad; Jacques Choucair (Journal of Infection in Developing Countries)
Introduction: We lack data on the epidemiology and management of brain abscesses in the Middle East. The aim of this study is to report a case series of brain abscesses admitted at a tertiary care center in Lebanon, between January 2008 and December 2018.